INTEGRATION METHODS: INTEGRATING SIMPLE AND RATIONAL FUNCTIONS - Boboqulova Durdona Sanjar qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This paper explores various methods of integration, focusing on the integration of simple and rational functions. These techniques form the foundation of integral calculus and are essential for solving problems in mathematics, physics, and engineering. The article discusses basic integration rules, substitution, and partial fraction decomposition, and provides examples demonstrating the practical application of these methods in evaluating definite and indefinite integrals.